On the Convergence of Absolute Summability for Functions of Bounded Variation in Two Variables. (30th December 2012) - Mei, Ying; Yu, Dansheng
Abstract : By adopting some new ideas, we obtain the estimates of an absolute convergence for the functions of the bounded variation in two variables. Our results generalize the related results of Humphreys and Bojanic (1999) and Wang and Yu (2003) from one dimension to two dimensions and can be applied to several summability methods.